INFLUENCE OF THE UNIFIED METHODOLOGY OF TEACHING PHYSICAL CULTURE WITH THE USE OF SPORTS BOARD GAMES ON THE FUNCTIONAL STATE OF THE ORGANISM OF STUDENTS OF A SPECIAL MEDICAL GROUP - Alexey Vladimirovich Kozlov; Anastasia Mikhailovna Katkova; Maria Alexandrovna Kozlova (Siberian journal of life sciences and agriculture, 2020)
Nowadays, in the system of scientific and practical knowledge, the question of developing the functional condition of students with HIA remains little studied. The article considers the important problem of health-saving technologies by means of introducing a unified methodology with the use of sports board games into the educational process of students assigned to a special medical group. The significance of the study is due to the fact that this unified technique is available to students in all types of pathologies, solves the problems of inclusive education, helps to increase motor activity, and as a result, it positively affects the functional indicators of the body of students of special medical groups (SMG). The study involved 406 students (17-20 years old). The experiment consisted of 3 stages. At each stage, the functional state of the condition was examined and the dynamics of the indicators for the Rufier Sample and Body Mass Index were monitored. The validity of the differences in the experimental data obtained at the 3 stages of the experiment was checked by: average arithmetic, percentage increase, Mann-Whitney U-criterion. The study showed that the applied technique is suitable for students with any type of deviations in the state of health and improves their functional condition of the body.